The Effect of β-Glucans from Oats and Yeasts on the Dynamics of Ice Crystal Growth in Acidophilic Ice Cream Based on Liquid Hydrolyzed Whey Concentrate - Mykhalevych, Artur; Polishchuk, Galyna; Znamirowska-Piotrowska, Agata; Kaminska-Dwórznicka, Anna; Kluz, Maciej; Buniowska-Olejnik, Magdalena (My University, 2025)
Improving the texture and shelf-life of whey-based ice cream remains a key challenge in clean-label food formulation. This study investigated the effects of different stabilizing ingredients–including Cremodan SI 320 (0.6%), oat β-glucan (0.25–0.5%), and yeast β-glucan (0.25–0.5%)–on the physicochemical properties and freezing dynamics of ice cream made from liquid hydrolyzed demineralized whey concentrate. Compared to Cremodan, oat β-glucan significantly lowered the freezing point, improved overrun, and enhanced melting resistance. Yeast β-glucan led to the smallest initial ice crystals (8.49 Ѓ} 0.37 μm) and minimal growth after one month (9.52 Ѓ} 0.16 μm), outperforming the control and Cremodan samples in crystal stability. The chemical composition and textural properties of each formulation were also evaluated. These findings demonstrate that oat and yeast β-glucans function as natural stabilizers, offering clean-label potential and improved structural integrity in frozen dairy desserts. Покращення текстури та терміну придатності морозива на основі сироватки залишається ключовим завданням у формулюванні харчових продуктів з дотриманням принципів «чистого етикетування». У цьому дослідженні досліджували вплив різних стабілізуючих інгредієнтів, включаючи Cremodan SI 320 (0,6%), вівсяний β-глюкан (0,25–0,5%) та дріжджовий β-глюкан (0,25–0,5%), на фізико-хімічні властивості та динаміку заморожування морозива, виготовленого з рідкого гідролізованого демінералізованого концентрату сироватки. Порівняно з Cremodan, вівсяний β-глюкан значно знизив температуру замерзання, покращив перетікання та підвищив стійкість до плавлення. Дріжджовий β-глюкан призвів до утворення найменших початкових кристалів льоду (8,49 ± 0,37 мкм) та мінімального зростання через один місяць (9,52 ± 0,16 мкм), перевершуючи контрольні зразки та зразки Cremodan за стабільністю кристалів. Також були оцінені хімічний склад та текстурні властивості кожної рецептури. Ці результати демонструють, що β-глюкани вівса та дріжджів функціонують як природні стабілізатори, пропонуючи потенціал для «чистої етикетки» та покращену структурну цілісність заморожених молочних десертів.
Keywords: кафедра технології молока і молочних продуктів; морозиво сироваткове; сироватка; чисте етикетування; whey ice cream; whey; clean labeling